Words for the Transitional Bubble: A Lexical Analysis of Two Economic Crises - Orts Llopis, María Ángeles; Rea Rizzo, Camino (International Journal of English Studies, 2011)
This study aims at the analysis of the lexicon in English of the two professional areas, telecommunications and finance, affected by the crises of the recent years: the 90s dot-com bubble and the present-day Credit Crunch. Both crises share a common context of wealth and cultural complexity, being the root for the coinage of innovative specialised terms and collocations. Our study is specifically aimed at unveiling the lexical coverage of both crises, in terms of technolects and their context, evolving in several phases. First, two corpora of specialised, semi-specialised and general texts from the domains’ digital periodicals will be characterized according to lexical relevance and terminological volume, to see the extent in which they are lexically connected or diverge when experiencing a critical situation like a crisis. Finally, clarifying how far these two disciplines have related during the last critical years will hopefully provide some clues for the lexical ethnography of two institutionalised ways of thinking.